IT disaster recovery and business continuity based on VMware SRM solution for Kuwait Oil Company (KOC) - Alshammari, Mohammad Matar; Alwan, Ali Amer (IEEE, 2016)
The IT center of Kuwait Oil Company (KOC) is one of the largest information centers in the State of Kuwait. It provides many services to KOC departments and other Kuwait oil sector companies (K-Companies). These services need to ensure High Availability (HA) and flexibility in their operations. The aim of this paper is to investigate the impact of the damage that affects the Business Continuity (BC) and data availability during and after disasters. The paper presents a VMware Site Recovery Manager (SRM) as a Disaster Recovery (DR) and BC solution with open-source to ensure HA of IT services at KOC. Moreover, the proposed solution introduces a better understanding of Disaster Recovery Plan (DRP) and Business Continuity Plan (BCP) methodology to enhance the KOC IT center by creating and validating a plan for maintaining continuous business operations before, during, and after disasters and disruptive events.